Corrosion inhibition performance and mechanism analysis of high-efficiency imidazoline quaternary ammonium salt on Q235 - WANG Pengjie; SONG Yuhao; FAN Lin; DENG Kuanhai; LI Zhonghui; MEI Zongbin; GUO Lei; LIN Yuanhua (Gongye shui chuli)
To further improve the corrosion inhibition efficiency in acid washing environments and reduce costs, an efficient bis-imidazoline quaternary ammonium salt(SMZB) compound was synthesized by using oleic acid, triethylenetetramine,and bromo-n-butane as raw materials. The corrosion inhibition performance and mechanism of SMZB on Q235 in 1.0 mol/L HCl solution were studied through methods such as weight loss experiments, electrochemical experiments, surface morphology, and theoretical calculations. The results showed that when the concentration of SMZB was 2.0 mmol/L, the inhibition efficiencies by weight loss experiment, EIS, and Tafel corrosion were 98.88%,98.15%, and 99.62%, respectively. Electrochemical experiments further proved that SMZB could adsorb on the surface of Q235 to form a stable protective film and further reduced the charge transfer rate within the corrosion system. SMZB was a mixed corrosion inhibitor that mainly suppresses the cathode and follows the Langmuir isotherm adsorption equation. Theoretical calculations indicated that the adsorption sites of SMZB were mainly located in the imidazole ring and Br-, and could spontaneously adsorb on the surface of Q235. SMZB exhibited excellent corrosion inhibition performance in a 1.0 mol/L HCl solution, which was mainly due to the formation of a stable protective film on the surface of Q235 and the reduction of the charge transfer rate within the system, thus providing excellent corrosion inhibition performance.